Damage detection in 3D truss structures using grey wolf optimization algorithm and natural frequencies - Ton-That, Hoang (Engineering Today, 2025)
This research presents the prediction of damage in 3D truss structures using the Grey Wolf Optimization algorithm (GWO). Natural frequencies are adopted as an objective function for optimization. To assess the behavior of 3D truss structures, a finite element model is used. The results, which are based on MATLAB code, are shown to validate the potential practical use of GWO.